2005
DOI: 10.1038/sj.bjc.6602665
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of Rad51 is an independent prognostic marker of survival in non-small-cell lung cancer patients

Abstract: High-level expression of Rad51, a key factor in homologous recombination, has been observed in a variety of human malignancies. This study was aimed to evaluate Rad51 expression to serve as prognostic marker in non-small-cell lung cancer (NSCLC). A total of 383 non-small-cell lung tumours were analysed immunohistochemically on NSCLC tissue microarrays. High-level Rad51 expression was observed in 29.4% (100 out of 340) of cases. Patients whose tumours displayed high-level Rad51 expression showed a significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(151 citation statements)
references
References 20 publications
7
143
1
Order By: Relevance
“…While no mutations have ever been detected in human cancers, in many tumors significantly up-or downregulated levels of RAD51 have been observed (Maacke et al, 2000;Henning & Sturzbecher 2003;Klein, 2008). Moreover, high-level expression of RAD51 is an independent prognostic marker of survival in non-small-cell lung cancer patients (Qiao et al, 2005). In addition, haematopoietic progenitor cells, when Rad51 is overexpressed showed elevated levels of chromosomal alterations, similar to those observed in tumors of the hematopoietic system (Francis and Richardson, 2007).…”
Section: 3mentioning
confidence: 72%
“…While no mutations have ever been detected in human cancers, in many tumors significantly up-or downregulated levels of RAD51 have been observed (Maacke et al, 2000;Henning & Sturzbecher 2003;Klein, 2008). Moreover, high-level expression of RAD51 is an independent prognostic marker of survival in non-small-cell lung cancer patients (Qiao et al, 2005). In addition, haematopoietic progenitor cells, when Rad51 is overexpressed showed elevated levels of chromosomal alterations, similar to those observed in tumors of the hematopoietic system (Francis and Richardson, 2007).…”
Section: 3mentioning
confidence: 72%
“…High expression of Rad51 in tumor tissues is associated with an unfavorable prognosis in lung cancer (Qiao et a1., 2005). A report showed that the downregulation of Rad51 in lung cancer cells could increase the chemosensitivity of cells to gemcitabine .…”
Section: Discussionmentioning
confidence: 99%
“…We observed increased RAD51 protein levels in MDA-hGH vs MDA-vector cell lines and T47D-hGH vs T47D-vec cell lines (Supplementary Figure 1, see section on supplementary data given at the end of this article). RAD51 overexpression has been demonstrated in numerous human tumour cell lines and primary tumour samples (Xia et al 1997, Ohnishi et al 1998, Maacke et al 2000a,b, Collis et al 2001, Raderschall et al 2002, Qiao et al 2005, Richardson 2005 and has been linked to reduced sensitivity to IR in numerous cell types, including breast cancer (Maacke et al 2000b, Russo et al 2008, Le Scodan et al 2010, prostate cancer (Collis et al 2001) and glioma (Ohnishi et al 1998). Elevated levels of RAD51 in breast cancer samples correlate with increased invasiveness and poor outcome in patients (Maacke et al 2000b, Russo et al 2008, Le Scodan et al 2010).…”
Section: N M Bougen Et Al: Autocrine Human Gh Is Radioprotectivementioning
confidence: 99%